Synthesis and properties of poly(hydroxamic acid) from crosslinked poly(methacrylate) - Haron, Md.Jelas; Wan Yunus, Wan Md Zin; Desa, Mohd Zaizi; Kassim, Anuar (Elsevier Science, 1994)
Poly(hydroxamic acid) chelating ion-exchange resin was prepared from crosslinked poly(methacrylate) beads. The starting polymer was prepared by a suspension polymerization of methacrylate and divinyl benzene. Conversion of the ester groups into the hydroxamic acid was carried out by treatment with hydroxylamine in an alkaline solution. Hydroxamic acid capacity of the product was 2.71 mmol/g. The resin exhibited high affinity towards Fe(III) and Pb ions and its capacities for Fe(III), Pb, Cu, Ni and Co ions were pH dependent. The ability of the resin to carry out the separation of Fe(III)CuCo/Ni and PbNi ions is also reported.